Agricultural production in the southern central Rif: between traditional practices and the desire for modernization and intensification: Taounate District as a model - Hini, Mohammed; El-Bazoui, Jaouad; Errafik, Mohammed (Journal of agricultural, environmental and veterinary sciences, 2025)
Traditional agriculture in the Taounate District has long been the primary economic activity and resource for the local population because of both the absence and limited importance of other activities. However, its weak returns -resulting from natural, organizational, and technical constraints- have altogether forced the state and local farmers to adopt production models that are based on modernization and intensification using what is available with the aim of increasing productivity and achieving regular and sustainable incomes. In this context, this study aims to highlight the reality of agricultural production in the Taounate district, between traditional practices and the desire for modernization and intensification. The study explores the transformations affecting agricultural production methods, including tools and inputs, the manifestations of agricultural intensification, and the yield of products. It also examines some of the constraints hindering modernization and intensification processes, In this paper, the descriptive and analytical approaches have adopted, based on a field norm survey of 840 farmers. The most important findings we have reached are summarized as follows: The early farmers’ move towards modernization and intensification; 50.8% of them currently rely on selected seeds, 89.9% use pesticides, 71.1% use chemical fertilizers, and 87.2% rely on threshing machines. As to crops, they have been diversified and intensified using what is available (cereals, fruit trees). Agricultural revenue has also witnessed some improvement, especially in the wet seasons, with an average of 17 tons/ha for cereals, 21 tons/ha for olives, and 17.6 tons/ha. However, this desire for intensification and modernization is facing natural and organizational constraints. Therefore, this study proposes reform at two levels: First, we suggest a transition from Dry agriculture to irrigated agriculture, providing a solution to the land problem, Second, we propose the necessity of establishing an industrial base to enhance the value of agricultural products and improve livestock breeds.